Från kolonisation till gruvexploatering: Nyttoperspektiv på naturen i Sápmi förr och nu - Andersson, Daniel; Cocq, Coppélie (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2016)
Nature is found at the centre of important placemaking processes in northern Sweden today. One example is conflicting discourses surrounding mining exploitations in reindeer herding areas. In this article, we discuss these processes in the light of the settler colonisation during approximately 1750–1850. Then, as well as now, a resource perspective on nature positions different ways of living of the lands against each other. Although the Swedish state in some regards have been replaced by global corporations, and the local people that are against the mines also turn the struggle to a global level, the situation today bears much in common with what happened during the colonisation in 18th and 19th centuries. We argue that a deeper understanding of contemporary processes – and their historical contexts – is needed in order to prevent conflicts and tensions between groups of people.